Kesantunan Dalam Pengajaran Bahasa Jepang - Luh Putu Krisna Damayanti (Program Magister Linguistik Universitas Udayana, 2014)
Politeness rules of conduct are established and agreed upon by a given society that civility as well as a prerequisite agreed by social behavior. This study aims to determine politeness in Japanese, especially the use of politeness in the classroom. Observations made ??in New Media Computer College who showed that in a social environment necessary to courtesy, especially in the educational environment. Politeness can be positive and negative politeness characterized by verbal politeness which is an activity in which the language reflected the values ??of courtesy / civility cultural values ??of an area. Nonverbal politeness is an act that is considered common according to benchmarks cultural values ??prevailing in society. The research was carried out with the data obtained from the inventory and observation, and then analyzed according to the theoretical foundation of the study. Data were collected, clarified and categorized to facilitate hypothesis testing. The test data was formalized in the form of verbal using symbols, and is in the form of informal descriptions. Communication has the objective to deliver the message of the speaker to the listener. Communication also aims to establish social relationships and the need to understand the socio-cultural aspects of both parties, as well as the ability to associate the phrase with situational contexts (context of situation), grammatical context (grammatical context), and the cultural context (cultural context) in which the conversation takes place.